Educational Leadership and Teacher Performance: Exploring the Impact of Instructional Management, Exemplary Conduct, and Staff Empowerment - Lokhananta Mutiara Rizqia; Wahyu Hidayat; Nandang Abdurohim (Journal of Educational Management Research, 2026)
This study aims to identify the level of madrasah principal leadership, determine the level of teacher performance, and examine the influence of principal leadership on teacher performance. A quantitative approach with a descriptive-associative design was employed. Data were collected through a structured questionnaire administered to 49 teachers using a saturated sampling technique. Data analysis included descriptive statistics, validity and reliability testing, normality testing, simple linear regression, t-test hypothesis testing, and coefficient of determination analysis. The findings indicate that madrasah principal leadership was categorized as high, with a mean score of 3.77, while teacher performance was also categorized as high, with a mean score of 4.00. Simple linear regression showed a positive and statistically significant influence of principal leadership on teacher performance (B = 0.532, t = 6.479, p < 0.001). The coefficient of determination (R² = 0.472) indicates that principal leadership explained 47.2% of the variance in teacher performance, while 52.8% was attributable to other factors. These findings imply that strengthening principal leadership, particularly through responsibility, exemplary conduct, and staff empowerment, can serve as an important pathway for improving teacher performance and supporting educational quality.